INFLUENCE OF ALIMENTARY DEFICIENCY OF POLYPHENOL ON THE CYTOMORPHOLOGICAL CHANGES IN THE ORAL CAVITY MUCOSA OF RATS - Nikolaeva, Anna (Journal of Education, Health and Sport, 2015)
The Aim of this research was to study the influence of chronic insufficiency of the plant polyphenols in the diet of of rats on the morphological changes in the epithelium of of the oral mucosa. Materials and methods. The experiment was conducted on 14 white female rats, which were in 2 groups by 7 animals. The rats of first group (intact) were kept on a standard diet of the vivarium, the second – were kept on a diet devoid of alimentary plant polyphenols. The experiment lasted 70 days. Results and conclusions. For the first time studied the value of alimentary plant polyphenols to morphofunctional state of the oral mucosa. It is found, that chronic deprivation the rats of the plant food caused significant disorders in epithelial layer - the violation of cell division, cell differentiation, the state of the microvasculature of the buccal mucosa.